Crumbs proteins stabilize the cone mosaics of photoreceptors and improve vision in zebrafish. (20th January 2021) - Hao, Qinlong; Zheng, Mingjie; Weng, Kechao; Hao, Yumei; Zhou, Yao; Lin, Yuchen; Gao, Feng; Kou, Ziqi; Kawamura, Shoji; Yao, Ke; Xu, Pinglong; Chen, Jinghai; et al.
Abstract: Although the unique organization of vertebrate cone mosaics was first described long ago, both their underlying molecular basis and physiological significance are largely unknown. Here, we demonstrate that Crumbs proteins, the key regulators of epithelial apical polarity, establish the planar cellular polarity of photoreceptors in zebrafish. Via heterophilic Crb2a-Crb2b interactions, the apicobasal polarity protein Crb2b restricts the asymmetric planar distribution of Crb2a in photoreceptors. The planar polarized Crumbs proteins thus balance intercellular adhesions and tension between photoreceptors, thereby stabilizing the geometric organization of cone mosaics. Notably, loss of Crb2b in zebrafish induces a nearsightedness-like phenotype in zebrafish accompanied by an elongated eye axis and impairs zebrafish visual perception for predation. These data reveal a detailed mechanism for cone mosaic homeostasis via previously undiscovered apical-planar polarity coordination and propose a pathogenic mechanism for nearsightedness.